The Impact of Motivation on Employee’s Job Performance: The Case of Kapital Bank OJSC. - Abdullayeva, Muzaya (ADA University, 2023)
The job performance of the workers is one of the most crucial factors in how well an organization performs. This makes it crucial to look into the variables influencing employee performance. To improve performance, it will be necessary to show how well employee motivation works as one of the aspects influencing employee performance. In this context, it was intended to investigate the impact of motivation on perceived job performance. The questionnaire method of data collection was applied to 72 employees of Kapital Bank branches operating in Baku, Azerbaijan. In this case, a questionnaire with scales for measuring job performance and motivation was distributed to the staff members working in the aforementioned bank branches. As a result of the study, it has been determined that the job motivation of the employees does not differ according to demographic variables, whereas the perceived job motivation differs according to gender and educational status of the employees. As a result of the simple regression analysis, it was revealed that job motivation together with its sub-dimensions such as intrinsic motivation and extrinsic motivation, are the significant determinants of the perceived job performance. On the top of that, it was found that intrinsic motivation is the most important determinant of the perceived job performance as per its explanatory power of 63.3%.
Keywords: Job performance; Intrinsic motivation; Extrinsic motivation; Business